2022
DOI: 10.3390/molecules27196460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Pretreatment on Flocculation Filtration of Low-Rank Coal Slurry

Abstract: The efficient filtration of low-rank coal (LRC) slurry was significantly beneficial to the production process of wet coal beneficiation. However, relatively few studies have been reported on novel pretreatment methods for the efficient filtration of LRC slurry. In this paper, the mechanism of ultrasonic pretreatment to promote flocculation and filtration of slurry was studied. The hydrophobic variation of the slurry surface was measured by contact angle and XPS. The flocculation properties of slurry were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Increasing the exposure time to ultrasonic waves reduced the size of the Chl particles and narrowed the distribution. The Chl particle size decreased with increasing ultrasound treatment time in agreement with Cao et al [90] and Yang et al [91]. After 0, 5, 10, and 15 min of exposure time, the average particle size was approximately 4.5 µm, 760 nm, 500 nm, and 10 nm, respectively.…”
Section: Dls Particle Sizesupporting
confidence: 89%
“…Increasing the exposure time to ultrasonic waves reduced the size of the Chl particles and narrowed the distribution. The Chl particle size decreased with increasing ultrasound treatment time in agreement with Cao et al [90] and Yang et al [91]. After 0, 5, 10, and 15 min of exposure time, the average particle size was approximately 4.5 µm, 760 nm, 500 nm, and 10 nm, respectively.…”
Section: Dls Particle Sizesupporting
confidence: 89%
“…Onal, Ozer, and Arslan (2003) reported that flocculant consumption and settling time decreased as a result of the use of ultrasound in clay flocculation. Burat, Sirkeci, and Onal (2014) and Yang et al (2022) found similar results in their studies focusing on the effect of ultrasonic treatment on the dewatering of fine coal, and stated that ultrasonic treatment improved flocculation and filtration performance. Few studies, however, have been conducted to investigate the effect of ultrasonic treatment on the shear flocculation of minerals with surfactants.…”
Section: Introductionmentioning
confidence: 59%
“…Viscosity and Permeability of APAM-Modified Soil Exponential functions were used for curve fitting of viscosity and perm periments, and the R-squared values for each curve were 0.990 and 0.971, r (Figure 8). It is noted that the viscosity of APAM solution may have a major water flow in seepage channels [34], and thus it can inhibit the migration of ext to the bottom of the ice lens. The APAM solution was influenced by the APA and it significantly thickened for the APAM concentrations higher than 1.5% This can increase the resistance of water migration and cause a decrease in th gration rate and frost heave rate.…”
Section: Viscosity and Permeability Of Apam-modified Soilmentioning
confidence: 99%